Analisis Faktor-Faktor yang Mempengaruhi Turnover Karyawan di Bank Mandiri Pekanbaru Sudirman Atas - Frilla Degustia; Marwansyah; Hermansyah (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the factors affecting employee turnover at Bank Mandiri Sudirman Atas Pekanbaru Branch. The phenomenon of increasing turnover from 8.5% (2021) to 12.7% (2023) has exceeded the 7% tolerance limit set by management, resulting in a 15% decrease in service performance and a 25% increase in recruitment costs. The research employed a quantitative approach with explanatory research method. The research population consisted of all 43 employees of Bank Mandiri Sudirman Atas Pekanbaru Branch, with sampling technique using census method. Data analysis used multiple linear regression with SPSS version 25 software. The results showed that all independent variables had positive and significant effects on employee turnover, both partially and simultaneously. Work stress was the factor with the largest influence (β=0.298), followed by organizational commitment (β=0.276), job satisfaction (β=0.245), work environment (β=0.223), and compensation (β=0.187). The research model was able to explain 76.7% of employee turnover variation (R²=0.767). These findings imply the need to prioritize stress management programs, strengthen organizational commitment, and review compensation systems to control employee turnover rates.